Hedonic Treadmill Syndrome, Financial Management Behavior, dan Generasi Milenial - Wirdaniya Binti Rohana; Sulis Rochayatun (Jurnal Ekonomi Akuntansi dan Manajemen, 2020)
The students consumptive behavior is the impact of increased consumption and economic growth. The continued impact of consumptive behavior is hedonism. Every student needs a tool called money to make ends meet as a student and his daily needs. However, the desire and dissatisfaction of students with what they already have can cause financial problems to arise, so that every student needs an increase in financial management behavior. Descriptive qualitative method with an interpretive approach is used in this research. This reserach aim to find out the students' hedonic treadmill syndrome and how to implement the concept of their financial management behavior considering the many cafes around UIN Malang. This study concluded that the environment affects students' hedonic treadmill syndrome. The meaning of the concept of financial management behavior by Accounting students of UIN Malang as a form of responsibility because their parents have entrusted them with pocket money. Thus, students feel they must be able to manage these funds, take them into account, distribute them properly, and use them logically. Keywords: Hedonic Treadmill Sundrome, Financial Management Behavior, University Student